2022
DOI: 10.2166/ws.2022.128
|View full text |Cite
|
Sign up to set email alerts
|

Jet flow in hydraulic-jump-stepped spillways: experimental study

Abstract: A hydraulic-stepped spillway was designed using an aeration basin to provide the aerated flow to the stepped spillway utilizing a hydraulic jump. However, the flow through the entrance of the stepped spillway might separate from the first step top and impact the downstream steps at a large unit discharge, causing a so-called jet flow. A new experimental study was conducted to better understand the jet flow in the hydraulic-jump-stepped spillway with comparisons to coventional stepped spillways. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The calculation of the hydraulic parameters of the lateral spillway is given in the works [7][8][9][10][11][12][13]. The results of calculating the differential waterworks [14][15][16][17] and the expanding part of the fast-flowing [18][19][20][21][22] are known. The design of the water well described in this article is unique.…”
Section: Fig 2 Plan Of Terminal Structurementioning
confidence: 99%
“…The calculation of the hydraulic parameters of the lateral spillway is given in the works [7][8][9][10][11][12][13]. The results of calculating the differential waterworks [14][15][16][17] and the expanding part of the fast-flowing [18][19][20][21][22] are known. The design of the water well described in this article is unique.…”
Section: Fig 2 Plan Of Terminal Structurementioning
confidence: 99%
“…The results revealed that bed water jets decreased jump length by an average of 48%. Zhou et al (2022) examined jet flow in hydraulic jumpstepped spillways. They stated that compared with conventional stepped spillways, the hydraulic jump-stepped spillway could extend the practical application for large unit discharges by providing a better understanding of jet flow conditions.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%